Hydrogen Absorption and Losses Characterization of Submarine Fiber Optic Caple - Namsongnern, K.; Yupapin, P.P. (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
The hydrogen induced attenuation increases in optical fiber cables has been tested and estimated. The increased spectrum attenuation of optical fiber cables is investigated by submersing the tested cables in ocean water tank for a period time. The increased attenuation in dB is characterized using monochromator and oscilloscope. The test procedure is intended to provide a test that is characterized the effect on fiber optic attenuation due to hydrogen generated by the cable components only, does not address the effect of hydrogen generated from sources exterior to the cable. The saturation of attenuation in dB is also determined. Keywords: fiber optic cable, fiber optic standard Corresponding author: E-mail: cast@kmitl.ac.th